Role of Sulforaphane in Protection of Gastrointestinal Tract Against H. pylori and NSAID-Induced Oxidative Stress - Yanaka, Akinori (Current Pharmaceutical Design, 2017)
Background: Sulforaphane (SFN), a phytochemical found in abundance in broccoli sprouts, potently induces a variety of antioxidant enzymes, and thereby protects cells from injury induced by various kinds of oxidative stresses. It has been suggested that both H. pylori infection and intake of non-steroidal anti-inflammatory drugs (NSAIDs) induce chronic oxidative stress in gastrointestinal (GI) mucosa, thereby causing mucosal injury in the GI tract. Therefore, it would be a reasonable assumption that SFN protects GI mucosa against oxidative injury induced by H. pylori or NSAIDs. Methods: We examined the effects of SFN on H. pylori viability in vitro, levels of gastritis in H.pylori-infected mice in vivo, and in H.pylori-infected human subjects. We also examined the effects of SFN on NSAID-induced small intestinal injury in mice. Results: Our data from the H. pylori infection study clearly demonstrated that SFN inhibited H. pylori viability both in vitro and in vivo, and mitigated H. pylori-induced gastritis in mice and humans. Similarly, our study on NSAID-induced small intestinal injury showed that SFN not only mitigated aspirin-induced injury of small intestinal epithelial cells in vitro, but also ameliorated indomethacin-induced small intestinal injury in mice in vivo. Conclusions: These data strongly suggest that SFN contributes to the protection of GI mucosa against oxidative injury induced by H. pylori or NSAIDs.
Keywords: small intestine